PENGGUNAAN KERIKIL PECAH SUNGAI KAHAYAN SEBAGAI ALTERNATIF AGREGAT KASAR PADA CAMPURAN HOT ROLLED SHEET-BASE (HRS-BASE) - Hendri Hermanto; Desriantomy Desriantomy; Salonten Salonten (INFO-TEKNIK, 2021)
Lataston is a mixture commonly used in Indonesia as a pavement structure. In its implementation in the field, implementers are often faced with the high use of aggregate in the Lataston mixture due to limited resources of crushed stone in Central Kalimantan, which usually forms the aggregate in the Lataston mixture imported from outside the region. Gravel from Menen Paduran Village has various grain sizes between 5 mm to 75 mm but has a surface that tends to be round and does not have an angular surface so that the gravel must be crushed using a Stone Crusher in order to meet the characteristics of coarse aggregate in the Lataston base layer mixture. The goal of this research was to find out how the usage of crushed gravel from Manen Paduran Village as coarse aggregate in the Lataston base layer mixture on the Marshall characteristic stability value in the foundation layer Lataston mixture (HRS-Base). The research was carried out in two parts, the first of which was to collect data. was making the test object using crushed gravel. Manen Paduran as coarse aggregate, ex stone ash. Peacock and Tangkiling sand as fine aggregate to obtain Optimum Asphalt Content (KAO). In the second stage is to make the test object using crushed stone ex. Peacock as coarse aggregate, ex stone ash. From the results of these tests, a comparison was made between the use of crushed gravel ex. Manen Paduran and crushed stone ex. Peacock seen from Marshall characteristics. Marshall test results using crushed gravel obtained an optimum asphalt content of 6.85%, Marshall test results obtained that the stability value decreased by 8.8% from the use of ex crushed stone. Peacock and with the use of crushed gravel ex. Manen Paduran is only